Clinically significant substance use and residential stability among homeless or vulnerably housed persons in Canada: a longitudinal cohort study. (19th February 2020) - Nasmith, Trudy E; Gadermann, Anne; Jaworsky, Denise; Norena, Monica; To, Matthew J; Hwang, Stephen W; Palepu, Anita
Abstract: Background: We examined clinically significant substance use among homeless or vulnerably housed persons in three Canadian cities and its association with residential stability over time using data from the Health and Housing in Transition study. Methods: In 2009, 1190 homeless or vulnerably housed individuals were recruited in three Canadian cities and followed for 4 years. We collected information on housing and incarceration history, drug and alcohol use, having a primary care provider at baseline and annually for 4 years. Participants who screened positive for substance use at baseline were included in the analyses. We used a generalized logistic mixed effect regression model to examine the association between clinically significant substance use and residential stability, adjusting for confounders. Results: Initially, 437 participants met the criteria for clinically significant substance use. The proportion of clinically significant substance use declined, while the proportion of participants who achieved residential stability increased over time. Clinically significant substance use was negatively associated with achieving residential stability over the 4-year period (AOR 0.7; 95% CI 0.57, 0.86). Conclusions: In this cohort of homeless or vulnerably housed individuals, clinically significant substance use was negatively associated with achieving residential stability over time, highlighting the need to better address substance use in this population.